Participación de las familias en la implementación del programa cuna más en la comunidad nativa Boras de Pucaurquillo, distrito de Pebas, provincia de Ramón Castilla 2022 - Vela Flores, Rayza Juliana (2023)
The research "PARTICIPATION OF FAMILIES IN THE IMPLEMENTATION OF THE CUNA MAS PROGRAM IN THE BORAS DE PUCAURQUILLO NATIVE COMMUNITY, DISTRICT OF PEBAS, PROVINCE OF RAMÓN CASTILLA 2022" had the objective of knowing the level of participation of families in the implementation of the Cuna Mas Program In the Boras de Pucaurquillo Native Community, the research was of a qualitative approach, descriptive level, ethnographic design, the population was 60 families from the Boras native community, as shown by 30 user families of the Cuna Mas Program of the Pucaurquillo Community.; As techniques, interviews and direct observation were applied. The level of participation of families in the Cuna Mas program is essential to achieve effective and sustainable results, it promotes capacity building, the exchange of experiences and mutual support. Through training, workshops, and counselling, families can learn about relevant topics, such as parenting, health, nutrition, education, and life skills.